2012
DOI: 10.1016/j.ajog.2012.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Placental pathology and long-term neurodevelopment of very preterm infants

Abstract: The objective of the study was to compare neonatal morbidity and long-term neurodevelopmental outcome between very preterm infants with placental underperfusion and very preterm infants with histological chorioamnionitis. STUDY DESIGN: We measured the mental and motor development at age 2 and 7 years in 51 very preterm infants with placental underperfusion and 21 very preterm infants with histological chorioamnionitis. RESULTS: At 2 years, very preterm infants with placental underperfusion had poorer mental de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 36 publications
4
46
1
Order By: Relevance
“…Despite remarkable differences in the severity of the fetal disease, early- and late-onset FGRs are both associated with poor long-term outcome from neurodevelopmental, cardiovascular and metabolic standpoints [21,22,23,32,33]. This supports the notion that regardless of the severity, chronic exposure to adverse intrauterine environment is critical to determine adverse fetal programming.…”
Section: Pathophysiological and Clinical Differences In Early-severe supporting
confidence: 65%
“…Despite remarkable differences in the severity of the fetal disease, early- and late-onset FGRs are both associated with poor long-term outcome from neurodevelopmental, cardiovascular and metabolic standpoints [21,22,23,32,33]. This supports the notion that regardless of the severity, chronic exposure to adverse intrauterine environment is critical to determine adverse fetal programming.…”
Section: Pathophysiological and Clinical Differences In Early-severe supporting
confidence: 65%
“…They also found fetal thrombotic vasculopathy to be associated with cerebral palsy. Obstructive umbilical cord abnormalities and placental infarction have been identified in cases of cerebral palsy of varying severity and presentations [5,8,[17][18][19]. To our knowledge, the association between isolated vascular compromise, as denoted by a combination of vasculopathy-coagulopathy, and IVH in ELBW infants was not reported before.…”
Section: Discussioncontrasting
confidence: 51%
“…In 19 of 27 studies, the patient characteristics were clearly differentiated between the CA and non-CA groups. In 15 out of these 19 studies, there was a significantly higher GA at birth among the non-CA group compared to the CA group [21,27,28,36,41,43,45,56,57,58,60,62,63,64,65]. Only 8 studies showed no difference among the groups in terms of GA [42,43,47,50,52,58,61,66].…”
Section: Methodsmentioning
confidence: 99%
“…The clinical profile of the infants and the methodological characteristics of the studies have been summarized in online supplementary appendix A (see www.karger.com/doi/10.1159/000357556 for all online suppl. material) [36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69]. …”
Section: Methodsmentioning
confidence: 99%